Model Of Cloud Accounting Adoption Among Indonesian Micro, Small And Medium Enterprises (Msmes) - Hamundu, Ferdinand Murni (2022)
Cloud accounting (CA) is an accounting information system that fits the characteristics of micro small and medium enterprises (MSMEs) for management accounting. MSMEs generally low uptake of management accounting and thus lead to the failure of the business. Meanwhile, MSMEs are considered the major contributor to the economic growth of most nations including Indonesia. This study has examined the effect of the Technololgy-Organization-Environment Framework (TOE) and Technology Acceptance Model (TAM) on the intention to adopt CA. The independent variables consist of cloud computing characteristics, organizational readiness, and environmental context such as industrial & market, mimetic pressures, as well as government intervention. In addition, the moderator variable consisted of perceived ease of use (PEU) and perceived usefulness (PU), whereas trust in the internet (TI and trust in system reliability (TS) as moderator variables. A quantitative method with non-probability purposeful sampling has been employed in this study. The population is MSMEs in Indonesia as GoFood merchants, with data collected of 345 responses. The result found PEU and PU have a mediating role between cloud computing characteristics, organizational readiness, industrial & market, mimetic pressures, and intention to adopt CA. In addition, TS has significantly moderated the relation between PEU and intention to adopt CA, while PU has been rejected. In short, the ownersmanagers of MSMEs are not concerned with the advanced internet, but more concerned with PEU, and TS. This study has highlighted the results and attempted to justify them with logic supported by the relevant literature.